Association between peripheral white blood cell count and autologous skin flap healing rate in rabbits - Husni, Norazlina (Universiti Sains Malaysia, 2015)
Successful skin flap survival depends on the rate of healing process, which can be related to the roles of white blood cells (WBC). Therefore, the aim of this study was to investigate the association between WBC count and autologous skin flap healing rate in rabbits. A total of four New Zealand White rabbits, aged between 9 to 15 months, were used in this study. All rabbits underwent autologous skin flap surgery at the ventral abdomen. A total of 3 ml of peripheral blood were collected from the central ear artery on day 0 (before surgery), day 1, 3, 5, 7 and 10 post-operation. The WBC count and manual WBC differential count were measured using Mythic 18 Vet Analyzer and Wright’s stain, respectively. The skin flap healing rates were determined by mean percentage of necrosis area at day 1, 3, 5, 7 and 10 post-operation. The results showed that the post-operative mean percentage of necrosis area was not significantly associated with the mean of WBC count. However, there was a decrease in the percentage of necrosis area and the WBC count showed normalization pattern on post-operative day 10. These changes could suggest successful wound healing process. This study showed that the pattern of WBC count changes could be used to evaluate the progress of wound healing in autologous skin flap surgery.